Health System in Iraq Post 2003 War - Lafta, Riyadh K. (AL-Kindy College Medical Journal, 2023)
Background: War represents a major human crisis; it destroys communities and results in ingrained consequences for public health and well-beingObjective: We set this study to shed light on the public health status in Iraq after the successive wars, sanctions, sectarian conflicts, and terrorism, in light of certain health indicators.Design: The primary source of data for this analysis comes from the Iraqi Ministry of Health, and The World Health Organization disease surveillance.Results: Most of the morbidity indicators are high, even those that are relatively declining recently, are still higher than those reported in the region. Common communicable diseases such as schistosomiasis, mumps, and measles continue to be a problem. Mumps showed two recent epidemics; in 2015, and in 2020. The same with respect to Measles. More than 40·% of the surveyed population showed both systolic and diastolic hypertension. Fasting glucose of 10·4% of the participants showed hyperglycaemia, only 6·5% of whom reported being diagnosed and treated as diabetic. The leading cancer in males is Bronchus and Lung cancer, followed by Colorectal, Urinary bladder, and Prostatic cancers while in females; Breast cancer is in the top of the list, followed by Thyroid, Colorectal, Brain, and Bronchogenic cancers. Rates for childhood cancers are obviously higher even than those in high-income countries.Conclusions: The struggling public health services in Iraq have been severely impacted by humanitarian and political crises and brutal armed conflict that resulted in restricted population access to food, clean water and basic services including healthcare and medicines.